Motywacje i powody wyjazdu na misje wśród misjonarzy przygotowujących się do wyjazdu - ATŁAS, TOMASZ (Annales Missiologici Posnanienses, 2010)
This article presents the results of the question and answer questionnaire form filled by the students of Center of Missionary Formation (Centrum Formacji Misyjnej) in Warsaw of the year 2009/10. They were asked among others to answer when they decided to go for missions, who suggested this or why they did so (what were their motives) as well as on whom they count for support (in prayer and on material help). This article is an general conclusion of their answers.